Evaluating The Efficiency Of Human Resources Information Systems Based On The Delone & Mclean (D&M) Modele 'A Field Study In The Directorate Of Administrative Development At Tishreen University' (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aimed to evaluate the efficiency of the human resources information system used in the Directorate of Administrative Development at Tishreen University, where the Delone and MacLean model used in evaluating the efficiency of information systems was relied upon.The data was collected based on a questionnaire designed from 39 phrases, it measure six dimensions on which the model is based: (system quality, information quality, service quality, user satisfaction, use, final benefit), and this questionnaire was distributed to workers in the directorate and university related to human resources, By relying on the comprehensive inventory method,129 questionnaires were analyzed by relying on a set of tests and statistical methods, including (SEM, one sample t test) using the program Spss /26/ and AMOS 23, and the research found that:The conditions for the efficiency of the model are achieved in the human resources information system at Tishreen University,The HRIS suffers from a decrease in the quality and availability of each of D&M dimensions.This study provided a set of recommendations that are based primarily on enhancing the availability of the studied dimensions through a set of proposed mechanisms, which will eventually lead to enhancing the efficiency of the human resource information system